2015
DOI: 10.1189/jlb.4a1214-603r
|View full text |Cite
|
Sign up to set email alerts
|

Rac1-dependent secretion of platelet-derived CCL5 regulates neutrophil recruitment via activation of alveolar macrophages in septic lung injury

Abstract: Accumulating evidence suggest that platelets play an important role in regulating neutrophil recruitment in septic lung injury. Herein, we hypothesized that platelet-derived CCL5 might facilitate sepsis-induced neutrophil accumulation in the lung. Abdominal sepsis was induced by CLP in C57BL/6 mice. CLP increased plasma levels of CCL5. Platelet depletion and treatment with the Rac1 inhibitor NSC23766 markedly reduced CCL5 in the plasma of septic mice. Moreover, Rac1 inhibition completely inhibited proteasePAR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 54 publications
1
54
2
2
Order By: Relevance
“…S14), we reasoned that Cxcr2 may drive renal neutrophil recruitment during infection in the absence of Cxcr1. To test this, we treated Cxcr1 −/− mice with vehicle or the selective Cxcr2 antagonist SB225002, which has been successfully used to inhibit Cxcr2-dependent neutrophil trafficking in mouse models of infection and inflammation in vivo (20,21). We found that Cxcr2 inhibition did not impair neutrophil accumulation in Candida -infected kidneys of Cxcr1 −/− mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S14), we reasoned that Cxcr2 may drive renal neutrophil recruitment during infection in the absence of Cxcr1. To test this, we treated Cxcr1 −/− mice with vehicle or the selective Cxcr2 antagonist SB225002, which has been successfully used to inhibit Cxcr2-dependent neutrophil trafficking in mouse models of infection and inflammation in vivo (20,21). We found that Cxcr2 inhibition did not impair neutrophil accumulation in Candida -infected kidneys of Cxcr1 −/− mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies indicate that, depending on the underlying pathology, PNAs are not always mediated by classic P-selectin/PSGL-1 binding, but rather by other receptor-ligand interactions or via soluble mediators. Indeed, in LPS-induced ALI platelet-derived CXCL4 and CCL5 control neutrophil infiltration via induction of CXCL2-release by alveolar macrophages (126,127). Furthermore, sequestrated platelets in the pulmonary microcirculation of TRALI-induced mice promote NET formation (128).…”
Section: Platelet-leukocyte Interactions In Pathologic Conditionsmentioning
confidence: 99%
“…Activated platelets also release CXCL4 and CCL5 from their α-granules that promote neutrophil accumulation in septic lungs in the coecal ligation and puncture model through the release of CXCL2 from alveolar macrophages [95,96]. On the other hand, neutrophil-derived cathepsin G can trigger platelet activation through the protease-activated receptor 4 (PAR4) and mediate intracellular calcium signaling [97].…”
Section: The Role Of Platelets and Stromal Cells In The Amplificationmentioning
confidence: 99%